Comparison of creating 3D models from UAV: Case study windmill Černilov - Jech, Jakub; Komárková, Jitka (IEEE (Institute of Electrical and Electronics Engineers), 2023)
Modern world wants to have realistic and precious real world models. One of the representations of the real world is 3d models. This paper compares approaches and processing time for creating a 3D model based on UAV-borne image data. Image data for 3D model was collected by two approaches by an UAV. Both approaches were controlled by planned flights with specific parameters. Creating 3D models was processed in two software tools. One of them was freeware, and the second one was licensed. Results from the processing of 3D models show different processing times and quality of 3D models given by tools and data collection approaches.
Porovnání tvorby 3D modelů z UAV: Případová studie větrný mlýn Černilov
Keywords: 3D model; 3D modelling; photogrammetry; drone; UAV; 3D model; 3D modelování; fotogrammetrie; trubec; UAV